IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING KELAS X DI SMAN 5 MALANG - Febby Yuliana Putri; Rosichin Mansur; Moh. Muslim (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
In educational process, learning model is an important component. One of that can help educators in the PAI learning process is to apply a learning model. One of the learning models applied by PAI teachers at SMAN 5 Malang in order to develop student skills is problem-based learning. Here the researcher chose SMAN 5 Malang as the place for the research action. Researchers used descriptive qualitative research methods. Regarding the results obtained, in the learning planning process the teacher makes a syllabus and lesson plans in the process of making lesson plans, the institution facilitates teachers by holding workshops for preparing lesson plans at the beginning of each semester. The implementation of teacher learning creates a lively class using a problem-based model that makes students excited in learning process and can achieve learning goals. Educators carry out reflection and assessments that are carried out not only at the end of the lesson but also at the mid-semester and end-semester assessments using both written, oral and practical tests.